New Korean wave transnational cultural power in the age of social media - Jin, Dal Yong 1964- (Urbana, Chicago University of Illinois Press, 2016)
"The 2012 smash "Gangnam Style" by the Seoul-based rapper Psy capped the triumph of Hallyu , the Korean Wave of music, film, and other cultural forms that have become a worldwide sensation. Dal Yong Jin analyzes the social and technological trends that transformed South Korean entertainment from a mostly regional interest aimed at families into a global powerhouse geared toward tech-crazy youth. Blending analysis with insights from fans and industry insiders, Jin shows how Hallyu exploited a media landscape and dramatically changed with the 2008 emergence of smartphones and social media, designating this new Korean Wave as Hallyu 2.0. Hands-on government support, meanwhile, focused on creative industries as a significant part of the economy and turned intellectual property rights into a significant revenue source. Jin also delves into less-studied forms like animation and online games, the significance of social meaning in the development of local Korean popular culture, and the political economy of Korean popular culture and digital technologies in a global context"--
"Since the 1990s Korea has emerged as a production center for transnational popular culture, with Western audiences enjoying local cultural genres like TV dramas and pop music (K-pop). From 1997 to 2007 the Korean Wave (Hallyu) focused on the export of film and TV programs. Hallyu after 2008 diversified amid changing digital technologies and cultural politics. Korean smartphones and social networks have become major components of Hallyu. As with Psy's "Gangman Style," social media have shifted the global cultural flow of popular culture. Jin analyzes the social and tech trends behind Hallyu's global reach, emphasizing the strong connection between technology-avid youth and fandom in different parts of the world. Jin argues for a distinction between Hallyu 1.0 and Hallyu 2.0, marking the emergence after 2008 of different cultural forms. He blends analysis on the export and reception of Korean films, pop music, TV programs, online gaming, and animation with insights from interviews with fans and media industry personnel to tell how the Korean cultural industry grew from a relatively overlooked sector to a global success story"--
Incluye referencias e índice.
Keywords: Medios de comunicación de masas; Innovaciones tecnológicas -- Aspectos sociales; Popular culture -- Korea (South) -- History -- 21st century; Ciencias sociales-Periodismo; Cultura popular y globalización